Kalibrasi 161 Jam Masjid di Kabupaten Rejang Lebong - Ridhokimura Soderi; Angga Ade Putra; Bintang M. Hakim; Imratul Nabila, Inka; Yuriza Mei Raseli (Jurnal Aksi Dosen dan Mahasiswa, 2024)
Clock calibration refers to the process of adjusting or resetting a clock or time device to conform to a predetermined time standard. This is done to ensure that the watch or device shows the time accurately and in accordance with applicable standards. The clock calibration process involves resetting the clock in mosques in Rejang Lebong district. This community service aims to increase the accuracy of the mosque's "clock" time indication as a benchmark for the entry of prayer times or breaking the fast, because this community service activity is carried out in welcoming the holy month of Ramdhan 1445 H.  The methods used include socialization of the use of calibration hours to the community, technical training to mosque administrators, and accurate data collection from several strategic points. The results of the calibration of the clock in the mosques of Rejang Lebong regency from 161 data show a significant percentage of only 28% of mosque clocks that are accurate or in accordance with the national reference clock, 38% of mosque clocks that are 1 minute behind the national standard reference clock, 16% of mosque clocks that are 2 minutes behind the national standard reference clock, 5% 3 minutes late,  3% 4 minutes late from the national reference time.